KUALITAS KOKON HASIL PERSILANGAN ANTARA ULAT SUTERA (Bombyx mory L.) RAS CINA DAN RAS JEPANG - Lincah Andadari; Sri Sunarti (Jurnal Pemuliaan Tanaman Hutan, 2015)
This study was aimed to get the qualified silkworm (Bombyx mory L.) stock by crossing between Chinese dan Japanese races. The materials used in this study were the best fourth lines of Chinese and Japanese silkworm races at Forestry Research and Development Agency, Bogor. Experimental design used in this study was Completely Randomized Design. The results showed that observed parameters were significantly affected by crossed combination. Sixteen crossedbreed combinations resulted were potensial to be selected as commercial stock compared to control BS-09.